Ciudades Sostenibles, Inclusivas y Resilientes: Gobiernos Locales y Participación Ciudadana en la Implementación de las Agendas Globales para el Desarrollo - Dávalos, Javier (2017)
The United Nations has promoted the adoption of global agendas for sustainable development as a guide for the establishment of local policies. The 2030 Agenda with its 17 Sustainable Development Goals and the New Urban Agenda are the international framework for most of the UN Member States and should be implemented simultaneously in each of the territories, in order to achieve local sustainable development. Both agree on the need to create inclusive, sustainable and resilient cities and on the condition of cities as key players in development